Special interest : teachers unions and America's public schools - Moe, Terry M. (Brookings Institution Press, 2011)
"Examines the history of teachers unions--their rise to power and the organizational foundations of that strength, use of collective bargaining and involvement in the political process, and unions' response to expanded use of technology in the classroom to teach children, and consequences for America's public schools"--Provided by publisher.